Answer:
y = 3x + 2
Step-by-step explanation:
Convert the equation to slope intercept form to get y = –1/3x + 2. The old slope is –1/3 and the new slope is 3. Perpendicular slopes must be opposite reciprocals of each other: m1 * m2 = –1
With the new slope, use the slope intercept form and the point to calculate the intercept: y = mx + b or 5 = 3(1) + b, so b = 2
So y = 3x + 2
Tell them what comes first and what comes last
Step-by-step explanation:
<em>Here, slope of the line (m) = 1</em>
<em>Here, slope of the line (m) = 1And, the line passes through the point (7,9)</em>
<em>Equation </em><em>of </em><em>the </em><em>line </em><em>is </em><em>given </em><em>by </em>
<em>y </em><em>-</em><em> </em><em>y1</em><em> </em><em>=</em><em> </em><em>m </em><em>(</em><em> </em><em>x </em><em>-</em><em> </em><em>x</em><em>1</em><em> </em><em>)</em>
<em>y </em><em>-</em><em> </em><em>9</em><em> </em><em>=</em><em> </em><em>1</em><em>(</em><em> </em><em>x </em><em>-</em><em> </em><em>7</em><em>)</em>
<em>y </em><em>-</em><em> </em><em>9</em><em> </em><em>=</em><em> </em><em>x </em><em>-</em><em>7</em>
<em>x </em><em>-</em><em>7</em><em>+</em><em>9</em><em>-</em><em>y</em><em> </em><em>=</em><em> </em><em>0</em>
<em>x </em><em>-</em><em> </em><em>y </em><em>+</em><em> </em><em>2</em><em> </em><em>=</em><em> </em><em>0</em><em> </em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>is </em><em>the </em><em>required </em><em>equation </em><em>of </em><em>the </em><em>line. </em>
Answer:
D
Step-by-step explanation:
I took the quiz and got it right.
Also, the equation is y > x/2 - 3